Comparative Study of Helical Compression Suspension Spring for Different Materials - Patil, Sujit S.; Karunasagar, Subodh; Shah, Shubham (Asian Journal of Engineering and Applied Technology, 2016)
One of the major problems faced by automobile industries in few decades is the fuel efficiency which is related to the weight of the vehicle. This has led to more research in light weight materials with same mechanical properties as that of conventional materials. The composite materials are serving this need. In this study the helical compression steel springs are replaced with that of composite materials. The composite materials used are E-glass/Epoxy and Carbon fiber/Epoxy. Spring analysis is done with FEA and results are compared with steel spring. The springs are manufactured and the experimental deflections are also measured. The study shows that the weight reduction achieved with composite spring. Thus, indicating that the composite material springs can be effectively used as replacement for heavy steel springs.